CHANGE IN BLOOD GELSOLIN CONCENTRATION IN RESPONSE TO PHYSICAL EXERCISE - Jan Górski; Robert Bucki; Marcin Baranowski; Barbara Długołęcka; Małgorzata Charmas; Małgorzata Żendzian-Piotrowska; Chih-Chieh Yu (Termedia Publishing House, 2013)
Plasma gelsolin (pGSN) produced by muscle is an abundant protein of extracellular fluids capable of severing actin filaments and eliminating actin from the circulation. Additionally, pGSN modulates the cellular effects of some bioactive lipids. In this study we test the hypothesis that hormonal and metabolic adaptations to exercise are associated with changes in gelsolin concentration in blood. Plasma samples were collected from twenty healthy males recruited from untrained (UT, n=10) and endurance trained (ET, n=10) groups that performed 30-60 minutes of exercise on a cycloergometer at a workload corresponding to 700of VO2max. Gelsolin concentration was determined by quantitative Western blot analysis with an anti-human gelsolin antibody. The gelsolin concentration in UT and ET subjects before starting exercise ranged from 104 to 330 and 163 to 337 µg•ml-1 respectively. After 30 minutes of exercise we observed a significant decrease of plasma gelsolin in the UT group (p<0.05) while the gelsolin concentration in the ET group rose on average from 244 to 271 µg•ml-1. However, this increase did not reach statistical significance. Endurance training might increase the ability of muscle tissue to express plasma gelsolin as part of an adaptive mechanism.